1998
DOI: 10.1086/306272
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Jets and Orbital Dynamics of the Supersoft X‐Ray Source RX J0019.8+2156

Abstract: Between 1994 July and 1997 February we monitored the optical spectrum of RX J0019.8]2156. This supersoft X-ray source is one of only two accreting white dwarfs in the Galaxy that are thought to be burning hydrogen on their surface as a consequence of a high rate of mass transfer from a binary companion. Accurate orbital ephemerides are derived from radial velocity measurements for the white dwarf, which are obtained from strong He II emission lines with a stable velocity semiamplitude of K \ 71.2^3.6 km s~1. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 23 publications
5
34
0
Order By: Relevance
“…This is particularly evident in the work of Deufel et al (1999), who show data for many minima. However, in their study of the jets in QR And, Becker et al (1998) found that the He II emission lines from the jets showed exactly the same phasing and amplitude as the central line (the one we have measured). They concluded that since the jets must be centered on the compact star, the central He II therefore outlines its orbital motion.…”
Section: Ow-dispersion Spectroscopysupporting
confidence: 63%
See 2 more Smart Citations
“…This is particularly evident in the work of Deufel et al (1999), who show data for many minima. However, in their study of the jets in QR And, Becker et al (1998) found that the He II emission lines from the jets showed exactly the same phasing and amplitude as the central line (the one we have measured). They concluded that since the jets must be centered on the compact star, the central He II therefore outlines its orbital motion.…”
Section: Ow-dispersion Spectroscopysupporting
confidence: 63%
“…The strongest emission line is He II j4686, a typically dominant line in SSS and X-ray binary spectra. Note that during these low-dispersion observations the satellite "" jet ÏÏ lines (e.g., Becker et al 1998 ;Tomov et al 1998 ;Cowley et al 1998) were not present.…”
Section: Ow-dispersion Spectroscopymentioning
confidence: 84%
See 1 more Smart Citation
“…In some of these objects as well as U Sco, nonspherical or jetlike mass ejections are suggested (Taylor et al 1989;Shore 2002). High-velocity bipolar outflows are reported in the supersoft X-ray source RS J0513Ϫ6951 (Crampton et al 1996;Southwell, Livio, & Pringle 1997;Hutchings et al 2002), and low-velocity bipolar jets are observed in a supersoft X-ray source (Becker et al 1998).…”
Section: ϫ8mentioning
confidence: 99%
“…Winds, on the other hand, are not so well collimated, and exhibit velocities ranging from approximately 10% to 100% of the WD escape velocity, v esc [14]. Evidence for the presence of outflows in the form of Doppler shifted emission features and P Cyg absorption features has been found in the optical spectra of 4 supersoft X-ray binaries [15,16,17,18,19]. The main Balmer lines of the galactic sources RX J0019.8+2156 and MR Vel , as well as the Large Magellanic Cloud (LMC) source RX J0513.9-6951, exhibit P Cyg absorption profiles, together with sharp Doppler-shifted emission features, which are ascribed to emission from collimated jets.…”
Section: Spectral Evidence Of Outflowsmentioning
confidence: 99%